Characterization of the complete chloroplast genome of Murraya exotica (Rutaceae) from Yunnan Province, China - Zhou, Ning (Mitochondrial DNA B Resour, 2021)
Murraya exotica L. (Rutaceae) has important horticultural and medicinal values. Here, we reported the complete chloroplast (cp) genome of M. exotica using the next-generation sequencing method. The cp genome is 160,179 bp in length, including a large single-copy region (LSC, 87,726 bp), a small single-copy region (SSC, 18,465 bp), and a pair of inverted repeats (IR) regions 26,994 bp. A maximum-likelihood phylogenomic analysis showed that M. exotica was sister to Murraya paniculate. These findings will provide useful information for further investigation of cp genome evolution in Murraya.